Different responses to nivolumab therapy between primary and metastatic tumors in a patient with recurrent hypopharyngeal squamous cell carcinoma. (February 2020) - Sato, Kiminobu; Ono, Takeharu; Sato, Fumihiko; Kawahara, Akihiko; Azuma, Koichi; Kawaguchi, Toshihiko; Akiba, Jun; Umeno, Hirohito
Abstract: We report the case of a 70-year-old man with primary and metastatic tumors, showing clinically progressive disease and complete response to nivolumab therapy, respectively. He underwent total pharyngo-laryngectomy, bilateral neck dissection, and reconstruction with free-jejunum after nivolumab therapy failure, and had no recurrent or newly arising lesions 8 months after the surgery. Immunohistochemistry analysis revealed that metastatic neck tumor with the clinical complete response to nivolumab showed higher PD-L1 expression with higher CD8+ TIL density, while primary lesion with progressive disease showed lower PD-L1 expression with lower CD8+ TIL density. This represents the first case reported on head and neck squamous cell carcinoma treated with salvage surgery after nivolumab therapy failure.